(untitled) (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2022)
Literary works are born from the thoughts of the authors. This thought arises from the author’s experience with their respective cultural backgrounds and concerns about phenomena that are not in accordance with their thoughts. The author then expresses it in a literary work. Nursisto’s novel Dredah Bekakak Gamping tells of a social conflict that arose as a result of elite suppression of the rights of indigenous people. Meanwhile, the anthology of Agraria Indonesia poetry is poems with the theme of the urgency of Indonesia’s agrarian situation which is far from justice and equality. The anthology of Agraria Indonesia poetry was written by authors with different age backgrounds from the western to the eastern part of Indonesia. In these two literary works, the author raises the same social criticism as an expression of his experience of the phenomenon of oppression. Therefore, this study aims to compare the relevance of social criticism of the Javanese novel Dredah Bekakak Gamping with social criticism contained in the anthology of Agraria Indonesia poetry. The theory used as the basis for comparison is the theory of intertextual studies which outlines the principle of similarity between the texts of literary works with one another. The method used is descriptive qualitative type and note-taking technique. There are 3 relevant aspects of social criticism presented by the author, among others; social critique of greed, oppression and crime.